Woodbine Willie: The Unsung Hero of World War One - Holman, Annette (Lion Hudson, 2013)
Intro -- Dedication -- Title Page -- Copyright -- Contents -- Introduction -- 1. Childhood and Education, 1883-1904 -- 2. Into the Church, 1905-14 -- 3. Worcester and War, 1914-16 -- 4. The Wandering Preacher, 1916-17 -- 5. Rough Rhymes, 1917-18 -- 6. On the Front Line Again, 1917-18 -- 7. The Hardest Part, 1918 -- 8. From Local Priest to National Preacher, 1919-21 -- 9. The National Figure, 1921-29 -- 10. More Books Including a Novel, 1923-29 -- 11. The Death of Studdert Kennedy, 1929 -- 12. The Man, His Message and His Methods -- Epilogue Personal Observations: Towards a Better Society -- Notes -- Bibliography